Evaluating the face and content validity of a Teaching and Learning Guiding Principles Instrument (TLGPI): a perspective study of Malaysian teacher educators - Azwani Masuwai,; Nor’ain Mohd Tajudin,; Noor Shah Saad, (School of Social, Development and Environmental Studies, Faculty of Social Sciences and Humanities, Universiti Kebangsaan Malaysia, 2016)
Teaching and Learning Guiding Principles (TLGP) describes an organization’s beliefs and philosophy pertaining to quality assurance and performance improvement which guides the ‘what’, ‘why’ and ‘how’ of its activities. It is also a statement on the scholarship of teaching and learning and a reference guide to good practice specifically for teacher education institutions. The purpose of this study was to evaluate the face and content validity of a Teaching and Learning Guiding Principles Instrument (TLGPI). An expert panel of nine academicians in the field of teacher education reviewed and rated the TLGPI for the relevance and representativeness of each item based on a dichotomous rating of favourable or unfavourable. Their ratings were used to seek an agreement between the two or more raters in Cohen’s Kappa Index (CKI) and also to calculate the Content Validity Index (CVI) values of each final item. The percentage inter-rater agreement yielded at 70% of agreement in CKI. Items with CVI greater than 0.78 were included in the final instrument. The final instrument contained 67 items of 5-point Likert scale multiple choice options, categorised under six thematic domains namely (1) intellectual excitement; (2) quality learning spaces; (3) constructive alignment; (4) international and cultural diversity; (5) climate of inquiry and critical reflection; and finally (6) nurture good values, attitude and behaviour. The finding supports the face and content validity of this 67-item questionnaire, hence could be further researched on construct validity.